A case of predominantly chief cell parathyroid adenoma showing early washout of 99mTc MIBI detected by single-photon emission computerized tomography-computed tomography (SPECT-CT) - K B Sricharan; Rayudu Amrutha Lakshmi; V S Krishna Mohan; Gali Sai Chandana; Ranadheer Manthri Gupta; Mutheeswaraiah Yootla; Tekchand Kalawat (Journal of Clinical and Scientific Research, 2021)
Parathyroid adenoma is a major clinical manifestation of primary hyperparathyroidism, which is usually diagnosed with invasive methods. In most of the cases delayed washout of radio tracer is appreciated on routine parathyroid scintigraphy. Exceptionally in some cases, early washout of tracer is seen which results in false negative parathyroid scintigraphy due to various factors such as expression of p glycoprotein, expression of multidrug resistant protein 1, small glands and presence of chief cells. We present a the case of a patient with parathyroid adenoma showed fast tracer clearance on delayed images but anatomically localized by the additional images using single-photon emission computed tomography-computed tomography (SPECT-CT). The anatomically localized structure further characterized by histopathological examination with presence of abundant chief cells, the cause of poor tracer retention and fast clearance in delayed images. Knowledge about differential presence of chief cells and oxyphilic cells in various parathyroid adenomas must be considered by nuclear physician to avoid false negative parathyroid adenoma.